İdarenin sivil havacılık faaliyetleri - Erol, Ömer Faruk (My University, 2017)
Sivil havacılığa ilişkin uluslararası andlaşmalar ve Devletlerin milli düzenlemeleri hava hukukunun oluşumunu sağlamıştır. ABSTRACT International treaties on civil aviation and the national regulations of the States have provided the formation of air law.
Keywords: Devletler hukuku, Hava; Hukuk ve mevzuat; İdare HukukuHava HukukuSivil Havacılık Administrative LawAir LawCivil Aviation; Sivil havacılık